(untitled) (Olhar de Professor, 2021)
This essay analyses the evaluation process of special needs students in the context of regular school. The discussion is based on data obtained in semi structure interviews with teachers and pedagogical coordinators of Middle and High School of three schools in the city of Rio de Janeiro. This theme is relevant in terms of the complexity of evaluate de academic achievement of students whose demands cannot be met by an education system structured towards homogeneity, based on a standardized, classifying and meritocratic evaluation model. Data analysis revealed the possibilities of favoring inclusion and learning by means of flexibility and individualization of teaching methods, developing pedagogical actions that provide evaluation criteria and procedures which consider the singular characteristics of each student, and that have as aim to improve the teaching-learning process.